Prevascularization of 3D printed bone scaffolds by bioactive hydrogels and cell co-culture - Kuss, Mitchell A. (J Biomed Mater Res B Appl Biomater, 2017)
Vascularization is a fundamental prerequisite for large bone construct development and remains one of the main challenges of bone tissue engineering. Our current study presents the combination of 3D printing technique with a hydrogel-based prevascularization strategy to generate prevascularized bone constructs. Human adipose derived mesenchymal stem cells (ADMSC) and human umbilical vein endothelial cells (HUVEC) were encapsulated within our bioactive hydrogels, and the effects of culture conditions on in vitro vascularization were determined. We further generated composite constructs by forming 3D printed polycaprolactone/hydroxyapatite scaffolds coated with cell-laden hydrogels and determined how the co-culture affected vascularization and osteogenesis. It was demonstrated that 3D co-cultured ADMSC-HUVEC generated capillary-like networks within the porous 3D printed scaffold. The co-culture systems promoted in vitro vascularization, but had no significant effects on osteogenesis. The prevascularized constructs were subcutaneously implanted into nude mice to evaluate the in vivo vascularization capacity and the functionality of engineered vessels. The hydrogel systems facilitated microvessel and lumen formation and promoted anastomosis of vascular networks of human origin with host murine vasculature. These findings demonstrate the potential of prevascularized 3D printed scaffolds with anatomical shape for the healing of larger bone defects.